Detecção de Mycobacterium lepra por PCR em "SWAB" nasal e "SWAB" da linfa do lóbulo da orelha de pacientes hansenianos - PONTES, Ana Rosa Botelho (Universidade Federal do Pará, 2013)
Recently some studies have used Polymerase Chain Reaction (PCR) technique for detection of the Mycobacterium leprae DNA, in diverse biological samples, demonstrating high sensitivity. The objective of this work was to evaluate the sensitivity of the PCR in the detection of M. leprae in nasal swab and lymph swab from ear lobe of leprosy patients and to compare the results of the PCR with the bacilloscopy and histophatology and multibacillary and paucibacillary forms of leprosy. Nasal secretion samples and lymph of the lobe of the ear of 24 leprosy patients had been collected. For amplification of the DNA three pairs of primers had been tested: S13 and S62, R1 and R2, LP1 and LP2 that amplify fragments of 531 DNA of pb, 372pb and 129pb, respectively. The primers LP1 and LP2 had expressed greater sensitivity, independent of the clinical samples. The results of the PCR had been highly significant for the nasal secretion samples (p<0.0000) and significant for specimens of lymph of the lobe of the ear (p=0.0000). Comparing the results of the PCR, using primers LP1 and LP2 and conservante lise 1, with the bacilloscopy and histophatology, the studies had pointed that the PCR, in nasal secretion samples, got greater sensitivity for the MBs forms (41,67%), followed of the bacilloscopy (25%) and histophatology (8,33%). In the PBs forms, sensitivity was considered same between the PCR and the histophatology (8,33%). The bacilloscopy did not present sensitivity (0%). In the samples of the lymph of the lobe of the ear, the bacilloscopy demonstrated to greater sensitivity for the MBs forms (25%), followed of the PCR (20,83%) and histophatology (16,7%). In the PBs forms, the PCR and histophatology had presented same sensitivity (4,17%). It did not have sensitivity in the bacilloscopy (0%). The PCR, although not to demonstrate a 100% sensitivity it is a tool with future perspectives to assist in the monitoring of the treatment and cure of the leprosy patients.